JESSELTON PHILHARMONIC ORCHESTRA (JPO) IN THE NEW NORMAL - Lee See Ling; Lee Chie Tsang Isaiah, (Jurnal Gendang Alam (GA), 2022)
The ongoing global Coronavirus pandemic (COVID-19) struck Malaysia in early March 2020 leading the government to introduce regulations on social distancing and gatherings. This has led to restrictions on all forms of music and arts-related events across the nation including workshops, concerts, and festivals. This paper examines how the Jesselton Philharmonic Orchestra of Kota Kinabalu, Sabah has restructured their musical activity in response to pandemic-related regulations through use of online platforms to keep the community and activities ‘alive’. In doing so, we hope to provide a model by which other music and arts organizations may overcome barriers and continue to reach out to their respective communities.